Time‐resolved multiparameter analytics on a cell‐free production platform for acyl‐CoA precursors. Issue 11 (18th October 2022) - Maehler, Dominic; Hoefgen, Sandra; Münchberg, Ute; Schmitz, Oliver J.; Rautschek, Julia; Huang, Ying; Freier, Erik; Valiante, Vito
Abstract: Cell‐free biosynthesis is emerging as a very attractive alternative for the production of market‐relevant molecules. The free combination of enzymes, regardless of where they are isolated from, raises the possibility to build more efficient synthetic routes but at the same time leads to higher complexity regarding the analysis of the different enzymatic steps. Here we present an analytical method for the real‐time analysis of acyl‐CoA blocks forming and consuming during multi‐step catalyses. We focused on malonyl‐Coenzyme A and acetyl‐CoA, which are the most used acyl‐CoA units for carbon chain elongations. By employing capillary electrophoresis, we could detect the decrease of educts and the formation of products in a time‐resolved fashion.